Flextural properties of 3D printed Copper-Filler Polylactic Acid (Cu-PLA) - Kesavarma, Seluraju; E. H., Lee; M., Samykano; K., Kadirgama; M. M., Rahman; A. G. N., Sofiah (IOP Publishing, 2020)
Fused Deposition Modelling (FDM) technology is among the lowest cost 3D printing technology for processing thermoplastic and composite materials. FDM has been highly used inadditive manufacturing due to its ability to process complex parts with accurate dimension and lowest cost possible. FDM technology has limited working temperature; hence the materials used in FDM such as polylactic acid (PLA) have a relatively low melting temperature. The drawback of these thermoplastic printed through FDM is the lack of mechanical strength and properties such as thermal and electrical conductivity to print functional part. These problems have led to the development of new composite filament for FDM technique. In this research, polymer-matrix composite (PMC) with 25 wt.% and 80 wt.% of copper reinforced polylactic acid (PLA) specimens have been printed with different infill patterns (Rectilinear, Grid, Concentric, Octagram-spiral, and Honeycomb) to study its flexural properties. The flexural test was carried out according to ASTM D790. This study found that there is a significant effect of the two parameters towards flexural properties. From the flexural test, the preliminary result of flexural strength and flexural modulus were obtained. The flexural strength is 25.98 MPa achieved by the 25 wt.% Cu composition specimens with Concentric infill pattern. The flexural modulus is 0.3306 GPa achieved by the 80 wt.% Cu composition specimens with Concentric infill pattern.